Current role of ultrasonography in the diagnosis of breast cancer - Díaz, Hubertino (2015)
In the last few years, thanks to high resolution lateral transducers advanced technology, harmonic imaging, color Doppler, panoramic vision, ultrasound contrast enhancement, three-dimension, breast ultrasound has become the most important imaging test complementary to mammography on breast lesions evaluation and in many cases (dense breasts, age below 35, and pregnancy) is the first line test with higher sensitivity and specificity. An updated review is performed on ultrasound findings of malignant and benign lesions and breast cancer, the bi-rads ultrasound classification (breast imaging reporting and data system), Doppler color, third-dimension (3D), lymph node metastasis, ultrasound screening approach and breast lesions with ultrasound guide.